Case-control study of the epidemiological and clinical features of human adenovirus 55 and human adenovirus 7 infection in children with acute lower respiratory tract infections in Beijing, China, 2008–2013 - Xu, Lili; Liu, Jun; Liu, Chunyan; Duan, Yali; Zhu, Yun; Xu, Baoping; Xie, Zhengde (BMC infectious diseases, 2018)
In adults, the emerging human adenovirus (HAdV) type 55 (HAdV-55) has been reported to cause more severe cases of adenovirus induced acute lower respiratory tract infections (ALRTIs) compared to other HAdV serotypes (HAdV-3, HAdV-7, HAdV-14). However, there is a dearth of comparative studies in children that address differences in the clinical epidemiological features between HAdV-55 and other HAdV serotypes that can also induce severe infection (such as HAdV-7). We conducted a retrospective review of pediatric patients hospitalized at Beijing Children's Hospital with ALRTI from April 2008 to December 2013 who had adenovirus detected from nasopharyngeal or throat samples by PCR. We further compared pediatric patients infected with HAdV-55 to those infected with HAdV-7 using a case-control methodology by matching each subject with HAdV-55 infection to 4 patients with HAdV-7 infection within 2 months of each HAdV-55 infection. Demographic, clinical, and etiological data were collected and analyzed. Over the five-year period, HAdV was detected in 194 children. Of these, 8 were HAdV-55 positive. Epidemiological results showed that HAdV-55 infection was observed only in 4% of adenovirus infected children whereas HAdV-7 infection proportioned 53%. Most cases of HAdV-55 infection were identified during March and April, whereas HAdV-7 infection occurred throughout the year. Wheezing was significantly less frequent in the HAdV-55 group. No patients infected with HAdV-55 presented with vomiting or had any underlying disease. Coinfections with other respiratory tract pathogens were frequent among children infected with either HAdV-55 or HAdV-7. HAdV-55 circulated in Beijing during spring and appeared to cause pediatric respiratory infections that were as severe as HAdV-7 infections. Broader surveillance studies are needed.